Pengaruh Melemahnya Nilai Tukar Rupiah Terhadap Tingkat Kesehatan Perbankan Syariah - Widiyanata, Dwi Cahya (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to observe the effect of the devaluation of Indonesian Rupiah on the level of risk-based bank rating of Islamic Banking in Indonesia. There are four factors studied; they are capital, asset quality, earnings and liquidity. These four factors are outlined in seven dependent variable (the ratio of CAR, EAQ, NOM, ROA, ROA, STM and FDR) and one independent variable (foreign exchange rate). This study uses MANOVA (Multivariate Analysis of Variance) to determine the effect. The result shows that the devaluation of Indonesian Rupiah does not significantly affect the level of risk based-bank rating of Islamic Banking. Based on the tests of Between-subject effects, the devaluation of Indonesian Rupiah does not affect asset quality and liquidity factors of Islamic banking significantly. Meanwhile the capital and earnings factor are significantly influenced by the devaluation of Indonesian rupiah.Keywords:  foreign  exchange  rate,  risk-based  bank  rating  of islamic banking, capital, asset quality, earnings, liquidity, MANOVA